(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The purpose of this study was to determine the usefulness of vocabulary awareness in strengthening the writing abilities of undergraduate engineering students. The investigation was carried out at Hyderabad’s Vidya Jyothi Institute of Technology. The inquiry began with the selection of 120 Computer Science Engineering students acquiring English Language communication skills in the Advanced Communication Skills Lab during their third year first semester (2018-19). To perform the research, the teacher divided the students into two equal groups.